Architectural decor and modern aspects of application - Kozhakova Гульмира (Рroblems of engineering and professional education, 2023)
This article reveals the architectural decor as a spectator element of the architectural-space in the middle of the city, and at the same time it is considered as an element of composition and a method of architectural aesthetic expression. The issue of the use of decor in the city center is also covered. It is studied on the example of the reconstruction project of residential building facades located on Respublika Ave. in Astana; types of illustrations are shown.